Adrenal histoplasmosis in an immunocompetant Individual– a rare case report - Chandra Das, Tapas; Maiti, Animesh; Kumar Basu, Ashish; Sinha, Anirban; Dey, Lakshmi; Devarbhavi, Praveen; Chakraborty, Satyam; Swar, Subir; Sinha, Neeraj; Bhattacharjee, Kingshuk (International Journal of Medical Research and Review, 2016)
Introduction: Disseminated histoplasmosis is common particularly among immunocompromised individuals, alcoholics and extremes of age. It is of concern because of the associated high morbidity and mortality. Asymptomatic adrenal involvement has also been described in 30 to 50 % of patients with disseminated histoplasmosis. We report a case of adrenal histoplasmosis in an immune-competent subject presenting with adrenal insufficiency. Case Report: A 49 years old Indian male presented with three months history of weakness, nausea and vomiting, mucocutaneous pigmentation and weight loss. Past medical history was significant for tuberculosis, for which he was incompletely treated. He was non-smoker, non-alcoholic and non-diabetic, with no history of sexual promiscuity. USG of abdomen revealed bilateral suprarenal mass, with right adrenal (48.3x 39.3mm) and left adrenal measuring (42.4 x 38mm). CECT scan of upper abdomen showed enlargement of both adrenal glands with right adrenal 44x25x43mm, left adrenal measuring 53x37x46 mm suggestive of adrenal adenoma. CT guided FNAC of right adrenal mass showed necrosis, many budding yeast cells having the morphology of Histoplasma capsulatum. The patient was treated with liposomal form of amphotericin –B 150 mg / day for two weeks followed by oral itraconazole 200mg BD for one year and hydrocortisone 25 mg/day in divided doses. After one month, there was gain in weight, pigmentation faded and nausea & vomiting disappeared. Conclusion: Adrenal histoplasmosis usually occurs in a setting of immunocompromised condition and in endemic area, but it does occur in immunocompetant hosts from non-endemic area, as in our case. It is prudent to obtain a cytological or histopathological examination to confirm the diagnosis so that appropriate treatment can be instituted to avoid fatal complications.